Individuality and function of chemical signals during conflict resolution of a mammal. Issue 1 (10th November 2021) - Zhang, Chunmian; Sun, Congnan; Lucas, Jeffrey R.; Gu, Hao; Feng, Jiang; Jiang, Tinglei
Abstract: Individual recognition via communication signals is a critical component of social behavior, and provides the basis of conflict resolution, territorial behavior, and mate choice. However, the function of chemical signals in mammalian individual recognition and conflict resolution has largely been unexplored despite olfaction being a dominant sensory modality in many mammalian species. Here, we describe behavioral tests designed to evaluate the potential role of forehead gland secretions during conflict related to territorial defense in male Great Himalayan leaf‐nosed bats. We used gas chromatography–mass spectrometry to quantify the chemical composition. Our results showed that forehead gland secretions contain 16 categories of compounds, including 84 volatile compounds. The concentrations of compounds and their categories differed significantly among individuals. Moreover, behavioral studies indicated that males can use chemical signals for individual recognition. Contests were staged between males with or without functioning forehead glands. Paired males without functioning forehead glands displayed more physical contact and longer contest duration compared with pairs with functioning glands. Moreover, males with a functioning gland were more likely to win in contests when paired with males without a functioning gland. These findings support a growing amount of evidence that chemical signals play a vital role in conflict resolution in mammals. Abstract : The function of chemical signals in mammalian individual recognition and conflict resolution has largely been unexplored despite olfaction being a dominant sensory modality in many mammalian species. Here, we describe behavioral tests designed to evaluate the potential role of forehead gland secretions during conflict related to territorial defense in male Great Himalayan leaf‐nosed bats. We used gas chromatography–mass spectrometry to quantify the chemical composition.